Amanita amplivelata, (Amanitaceae, Agaricales), a remarkable new Eurasian species of the section Vaginatae - Hanss, Jean-Michel; Bozok, Fuat; Assyov, Boris; Yarar, Mahmut; Borovička, Jan; Ševčíková, Hana; Corriol, Gilles; Moreau, Pierre-Arthur; Taşkin, Hatira (Phytotaxa, 2024)
Amanita amplivelata is introduced as a new species, based on numerous collections from geographically distant areas of Europe and the Near East (Bulgaria, the Czech Republic, France and Türkiye). This new species is likely ectomycorrhizal with Populus spp. in natural poplar stands, urban settings, and plantations. Detailed description and illustrations of its morphological features are presented. Phylogenetic analysis of nrITS and combined nrITS, nrLSU and TEF-1α sequences placed it in a separate stirp in Clade 5 of section Vaginatae. The ample, saccate volva with a peculiar microscopic architecture confirms relatively close phylogenetic relationships with A. crocea and A. dryophila. The distinction of the new species from other phylogenetically related or morphologically similar taxa is outlined.